(untitled) (Journal of Comparative & International Higher Education, 2024)
This article examines the current thrust to digitalize higher education in Zimbabwe as the country strives to attain its vision to become an upper middle-income economy by 2030. In this regard, Innovation and Industrialisation have been added as missions of special emphasis at all education levels. This entailed that Higher Education Institutions (HEIs) adopt the Education 5.0 model and accelerate digitalisation of their operations and curricula. Further impetus of the digitalisation drive emerged from the responses to the COVID-19, such as lockdowns and travel restrictions. This article examines the policy framework that was put in place to digitalise curricula and operation systems in HEIs. A desk review of literature was conducted to examine efforts underway to embrace digitalisation as a new feature and future of higher education. The study established that the majority of institutions have tended to adopt externally developed digitilisation models without adequately adapting them to local circumstances. The study recommends the need for distinct digitalisation policies at both Ministry and HEIs levels, to guide and prepare for the ‘disruptive’ effects of digitalisation.